Implementation of the Principle of Justice for Crime Victims in the Criminal Procedure Process in Indonesia Based on the Perspective of Natural Law Philosophy - Fahrizal S.Siagian (JUSTICES: Journal of Law, 2025)
The implementation of the principle of justice for crime victims in the criminal justice process is a crucial issue in efforts to reform criminal law in Indonesia. The perspective of Natural Law Philosophy provides a strong normative foundation through the idea that every human being has natural rights that must be respected by the state, including the right of victims to obtain just redress. This study examines the extent to which Natural Law principles, such as moral justice, respect for human dignity, and balance of rights, are reflected in policies and practices for protecting crime victims. The method used is a normative juridical approach through analysis of relevant laws and regulations, doctrines, and court decisions. The results of the study indicate that although positive legal instruments such as the Witness and Victim Protection Law, provisions on restitution and compensation, and assistance mechanisms have accommodated victims' rights, their implementation remains inadequate. Barriers arise in the form of limited access, minimal understanding among law enforcement officials, and suboptimal service providers. These imperfections create a gap between the ideals of natural justice and positive sentencing practices. This research emphasizes the need to prioritize reformulating sentencing policies that are more oriented toward victim recovery so that the Indonesian legal system aligns with the universal values of Natural Law Philosophy and is able to deliver substantive justice in every law enforcement process.